2015
DOI: 10.1016/j.apenergy.2015.08.075
|View full text |Cite
|
Sign up to set email alerts
|

Performance analysis of the micro gas turbine Turbec T100 with a new FLOX-combustion system for low calorific fuels

Abstract: h i g h l i g h t sA new FLOX-combustion system has been successfully tested in a micro gas turbine. The operating performance of the Turbec T100 with LCV fuels was characterized. Reliable start-up and steady-state operation from 50 to 100 kW el was observed. Low emissions over the whole operating range: CO < 30 ppm, NO x < 6 ppm, UHCs < 1 ppm . The pressure drop across the combustion system was below 4%. g r a p h i c a l a b s t r a c t 80 82 84 86 88 90 92 94 96 98 100 0 5 10 15 20 25 30 35 40 45 50 551°C 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(31 citation statements)
references
References 27 publications
1
29
0
Order By: Relevance
“…Therefore, the carbon mole fraction of the exhaust gas can be compared with the fuel carbon mole fraction. Previous analysis of other gas turbine rigs have shown that the carbon balance approach gives very reliable exhaust gas mass flows [13]. The carbon balance equation was formed using the carbon mole fraction of C 12 H 23 , as the Jet A-1 surrogate (x f = 12 mol C/mol Kerosene), and the mole fraction of carbon in the exhaust gas (x ex = mol C/mol Exhaust Gas), as shown in Eqn.…”
Section: Thermodynamic Properties Mass Flowsmentioning
confidence: 99%
“…Therefore, the carbon mole fraction of the exhaust gas can be compared with the fuel carbon mole fraction. Previous analysis of other gas turbine rigs have shown that the carbon balance approach gives very reliable exhaust gas mass flows [13]. The carbon balance equation was formed using the carbon mole fraction of C 12 H 23 , as the Jet A-1 surrogate (x f = 12 mol C/mol Kerosene), and the mole fraction of carbon in the exhaust gas (x ex = mol C/mol Exhaust Gas), as shown in Eqn.…”
Section: Thermodynamic Properties Mass Flowsmentioning
confidence: 99%
“…Although increasing reactant dilution level results in lowering the combustion temperature, a higher dilution level is more beneficial to fully oxidizing air/fuel mixture and reduction of NO concentrations . To examine this effect, the molar fraction of CO and NO were selected to represent the outlet product concentrations for the present study, as shown in Figures and for CO and NO, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Several combustion techniques have been proposed to handle these problems, such as porous media and cyclone combustion system . A few investigations on PG flameless combustion can be found in literatures . Integration of flameless combustion with PG will be an outstanding achievement for reducing emissions and dependence on fossil fuels in the combined heat and power generation system.…”
Section: Introductionmentioning
confidence: 99%
“…8 Combustion process operated under lean-fuel conditions with combustion air at 650°C. The combustor was designed to provide intensive combustion product recirculation to achieve internal dilution and preheat the fresh reactants.…”
Section: Introductionmentioning
confidence: 99%
“…Another PG flameless combustor known as flameless oxidation burner was tested with a microgas turbine. 8 Combustion process operated under lean-fuel conditions with combustion air at 650°C. The result shows that although the heating value of PG decreased from 5 to 3.5 MJ/kg, the gas turbine achieved stable operation with constant efficiency.…”
Section: Introductionmentioning
confidence: 99%